2011
DOI: 10.1111/j.1752-8062.2011.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Skeletal Muscle Indicators of Mitochondrial Structure and Biogenesis in Patients with Type 2 Diabetes and Heart Failure: Effects of Epicatechin Rich Cocoa

Abstract: Abstract(-)-Epicatechin (Epi), a fl avanol in cacao stimulates mitochondrial volume and cristae density and protein markers of skeletal muscle (SkM) mitochondrial biogenesis in mice. Type 2 diabetes mellitus (DM2) and heart failure (HF) are diseases associated with defects in SkM mitochondrial structure/function. A study was implemented to assess perturbations and to determine the effects of Epi-rich cocoa in SkM mitochondrial structure and mediators of biogenesis. Five patients with DM2 and stage II/III HF co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 15 publications
4
108
2
1
Order By: Relevance
“…The protective effect of EPI may occur via a reduction in oxidative stress, and improvement of mitochondrial structure and function [15-17]. Previous studies have also revealed that EPI-rich cocoa treatment improved mitochondrial structure and enhanced cardiac and/or SkM muscle function in patients with heart failure [18]. Furthermore, some studies have indicated that the epicatechin conjugate (EGCG) can alleviate cardiomyocyte hypertrophy [30-32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect of EPI may occur via a reduction in oxidative stress, and improvement of mitochondrial structure and function [15-17]. Previous studies have also revealed that EPI-rich cocoa treatment improved mitochondrial structure and enhanced cardiac and/or SkM muscle function in patients with heart failure [18]. Furthermore, some studies have indicated that the epicatechin conjugate (EGCG) can alleviate cardiomyocyte hypertrophy [30-32].…”
Section: Discussionmentioning
confidence: 99%
“…EPI treatment also improved mitochondrial structure in enhanced cardiac and/or SkM muscle function in patients with heart failure. Moreover, EPI increased the protein expression of SIRT1 [18]. Taken together, these results indicate a beneficial role for EPI in cardioprotective function and specifically in the protection of heart failure.…”
Section: Introductionmentioning
confidence: 97%
“…In humans (Taub et al, 2012), the administration of an epicatechin-rich cocoa (total epicatechin was 100 mg/day during 3 months) to patients with type 2 diabetes and heart failure stimulates mitochondrial biogenesis in skeletal muscle biopsies, as expressed by an increment in SIRT1-dependent activation of PGC-1a and as an elevation in mitofilin, porin, and mitochondrial complexes I and V protein levels. The long-term effect of curcumin, a dietary polyphenol derived from turmeric has been investigated on various markers of mitochondrial biogenesis.…”
Section: Polyphenols and Other Natural Productsmentioning
confidence: 99%
“…They showed that the beneficial effect of epicatechin could be due in part to protection of mitochondria (36). Huttemann et al (18) also recently reported that epicatechin could maintain exercise-induced mitochondrial capacity in the hindlimb muscles of mice even after discontinuation of exercise.…”
mentioning
confidence: 99%
“…Recently, Villarreal's research group (28,31,32,36,41,42) has examined the effects of epicatechin in the setting of cardiovascular disease. They showed that the beneficial effect of epicatechin could be due in part to protection of mitochondria (36).…”
mentioning
confidence: 99%